Pelatihan Kewirausahaan Pupuk Organik Cair (POC) dari Limbah Sampah Organik Rumah Tangga Bagi Kader Aisyiyah Desa Kalipetung, Kecamatan Wangon, Banyumas, Jawa Tengah: Pelatihan Kewirausahaan Pupuk Organik Cair (POC) dari Limbah Sampah Organik Bagi Kader Aisyiyah Desa Kalipetung, Kabupaten Banyumas - Anis Shofiyani; Hadi Pramono; Hamami Alfasani Dewanto (Universitas Muhammadiyah Palembang, 2025)
This community science and technology program is centered in PRA Kalipetung, Klapagading Village, Wangon District, Banyumas Regency, and collaborates with Aisyiah cadre as partners. A significant challenge found during the liquid organic fertilizer (LOF) entrepreneurship training was the lack of knowledge and skills of partners in producing LOF from household organic waste. In addition, they also lack basic accounting skills and product marketing strategies. To overcome this, technology transfer is needed that focuses on processing organic waste into LOF in a sustainable manner and is suitable for household production, which ultimately provides economic benefits. The purpose of this community science and technology program is to equip participants with knowledge and skills in making LOF, as well as basic accounting practices and marketing of LOF products. The approach used in this program includes counseling, training, and the creation of LOF entrepreneurship demonstration plots. The evaluation results showed an increase in participants' understanding of various aspects of the training. Specifically, the improvements that occurred included the objectives of the activity (60.71%), techniques for making liquid organic fertilizer (53.57%), materials used (53.57%), packaging techniques (42.85%), benefits for plants (63.71%), calculation of production costs from agricultural waste (64.43%), calculation of profitable selling prices (64.43%), accounting processes for calculating profit and loss (57.14%), marketing techniques (53.57%), and understanding market share (46.43%). In conclusion, the evaluation results show that participants have successfully understood the training material related to LOF entrepreneurship.